How Should We Treat Severe Malaria in the Setting of Artemisinin Partial Resistance? - Philip J. Rosenthal; Moses R. Kamya; Ruth Namazzi; Chandy C. John (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Artemisinin partial resistance (ART-R) threatens the control of falciparum malaria, but its impact on the treatment of severe malaria has been unclear. Two recent studies in Uganda have considered associations between PfK13 mutations linked to ART-R and treatment outcomes in children hospitalized with complicated or severe malaria and treated with intravenous artesunate. Children infected with ART-R parasites experienced delayed parasite clearance compared to those infected with drug-sensitive parasites. However, clinical outcomes, including mortality, length of hospital stay, incidence of subsequent febrile illness, and incidence of readmission did not differ between children infected with ART-R or drug-sensitive parasites. Therefore, at present treatment with intravenous artesunate should remain the standard-of-care to treat severe malaria in sub-Saharan Africa, even in the setting of ART-R, although continued study of treatment efficacy is warranted.